Why ASEAN Could Stay Strong? - Dinna Wisnu (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2013)
How confident are ASEAN as a regional organization? Will ASEAN turn into a mere coffee-talk forum? This article evaluates the bases for ASEAN and demonstrates that ASEAN has reasons to stay strong as regional cooperation. Rather than denying tensions, this article agrees that there are tensions among members but it also recognizes such challenge as the one that unites ASEAN members together. There are some dilemmas among members of ASEAN that does not left much room for members but to cooperate with each other: the dilemma of risking higher tensions among members, the dilemma of risking the benefits of existing pooling of resources, the dilemma of improving connectivity among members and the dilemma of facing global pressure on good governance and liberal democracy.